The analysis of homologous recombination pathways in Saccharomyces Cerevisiae - Tay, Y (2010)
Homologous recombination (HR) is essential for the repair of DNA doublestrand breaks (DSBs) and damaged replication forks. However, HR can also cause gross chromosomal rearrangements (GCRs) by producing crossovers (COs), resulting in the reciprocal exchange of sequences between non-sister chromatids. Therefore, HR-mediated GCRs are suppressed via the promotion of HR pathways that favour noncrossover (NCO) formation, such as the synthesis-dependent strand annealing (SDSA) and dissolution pathways, which are modulated by Mph1 and Sgs1 helicases, respectively. The mismatch repair (MMR) pathway is intricately associated with HR via its roles in repairing mismatches on heteroduplex DNA that can arise during HR and in preventing homeologous recombination. Using a plasmid break-repair assay, we have revealed a novel, MMR-independent role of MutSα in promoting the formation of a subset of COs that is specifically supressible by Mph1, during HR between two completely homologous sequences. In contrast, the MMR-dependent function of MutSα, together with Mph1 and Sgs1, was shown to be required for the suppression of CO formation during homeologous recombination. These data indicate that Mph1 can both antagonise and promote the functions of MutSα during DSB repair, depending on the levels of homology between the two recombining sequences. COs are generated by the resolution of Holliday junction (HJ) intermediates formed at the terminal stages of HR. Several S.cerevisiae proteins such as Yen1, Mus81, Slx1 and Rad1 have been implicated in HJ resolution. However, the in vivo roles of these proteins in HJ resolution remain to be confirmed. To directly and quantitatively monitor in vivo HJ resolution in S.cerevisiae, a transformation-based HJ resolution assay using a plasmid-borne HJ substrate has been developed. Using this system, we have demonstrated an in vivo HJ resolution function of Yen1, which acts redundantly with Mus81. Moreover, these redundant activities of Yen1 and Mus81 are essential for survival during replication stress, but are dispensable for DSB repair. An Slx4 and Rad1-dependent in vivo HJ resolution activity was also observed in the absence of Yen1 and Mus81 that was suppressed by presence of Slx1. Models describing how the nucleases interact to process HJs in vivo will be discussed.